Proteomic profiles and cytokeratin 13 as a potential biomarker of Ovis aries papillomavirus 3-positive and negative cutaneous squamous cell carcinomas. (January 2021) - Vitiello, Veronica; Burrai, Giovanni P.; Pisanu, Salvatore; Cacciotto, Carla; Addis, Maria Filippa; Alberti, Alberto; Antuofermo, Elisabetta; Cubeddu, Tiziana; Pirino, Salvatore
Abstract: Ovis aries papillomavirus 3 (OaPV3) is an epidermotropic PV reported in sheep cutaneous squamous cell carcinoma (SCC). The presence of OaPV3 DNA and its transcriptional activity in cutaneous SCC, as well as its in vitro transforming properties, suggest a viral etiology for this neoplasm. Nevertheless, the reactome associated with viral-host interaction is still unexplored. Here, we investigated and compared the proteomic profiles of OaPV3-positive SCCs, OaPV3-negative SCCs, and non-SCC samples by liquid chromatography tandem-mass spectrometry (LC-MS/MS) analysis, bioinformatics tools, and immunohistochemistry (IHC). OaPV3-positive SCCs ( n  = 3), OaPV3-negative SCCs (n = 3), and non-SCCs samples (n = 3) were subjected to a shotgun proteomic analysis workflow to assess protein abundance differences among the three sample classes. Proteins involved in epithelial cell differentiation, extracellular matrix organization, and apoptotic signaling showed different abundances in OaPV3-positive SCCs tissues ( P  ≤ 0.05) when compared to the other tissues. Cytokeratin 13 (CK 13) was among the most increased proteins in OaPV3-positive SCC and was validated by immunohistochemistry on 10 samples per class, confirming its potential as a biomarker of OaPV3 infection in SCC. Collectively, results provide a preliminary insight into the reactome associated with viral-host interaction and pave the way to the development of specific biomarkers for viral-induced sheep SCC. Highlights: Deregulation of proteins related to Papillomavirus infections are important findings in a subset of cutaneous and mucosal animal tumor. Sheep squamous cells carcinoma represents the most common form of skin tumor. Papillomavirus may play a role in the etiology of ovine cutaneous squamous cells carcinoma (SCC). CK 13 is a promising putative biomarker of Ovis aries Papillomavirus 3 infection in ovine cutaneous SCC.